2023
DOI: 10.3390/jcm12062270
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Hyperbaric Oxygen Therapy in Reducing Long-Term COVID-19 Sequelae?

Abstract: The COVID-19 pandemic has plagued our society for approximately three years [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…3,10 HBOT has been proposed as a potential therapy to address the effects of hypoxia contributing to these symptoms. 11 An initial study was conducted in 2021; since then, more research is assessing the therapy with more rigorous study designs. 12 Post-COVID-19 condition is a complex health condition that presents an important challenge to health care decision-makers in Canada…”
Section: Who Might Benefit?mentioning
confidence: 99%
“…3,10 HBOT has been proposed as a potential therapy to address the effects of hypoxia contributing to these symptoms. 11 An initial study was conducted in 2021; since then, more research is assessing the therapy with more rigorous study designs. 12 Post-COVID-19 condition is a complex health condition that presents an important challenge to health care decision-makers in Canada…”
Section: Who Might Benefit?mentioning
confidence: 99%
“…Fourteen medical applications have been accepted by UHMS [20]. Recent clinical and preclinical results have suggested the potential usefulness of HBOT in treating long COVID-19 [21][22][23][24][25][26][27][28][29][30][31]. In particular, in neurological tissues, Zilberman-Itskovich et al (2022) [32] provided some interesting observations about the effects of hyperbaric therapy on perfusion; in myocardial function, Leitman et al (2023) [27] suggested that HBOT can indicate subclinical left ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%